Analisis Etis dan Yuridis Perundungan Terstruktur Dalam Sistem Pendidikan Kedokteran Spesialis: Ethical and Legal Analysis of Structured Bullying In The Specialist Medical Education System - Lovinska, Arlyne Faza; Wicaksono, Emirza Nur; Khasanah, Dian Ratu Ayu Uswatun (Magister Ilmu Hukum - Universitas Hang Tuah, 2025)
The phenomenon of bullying within the specialist medical education system is a serious issue rooted in the rigid and closed hierarchical structure of teaching hospitals. This form of bullying not only threatens the mental health of medical residents but also raises profound concerns from the perspective of medical professional ethics and applicable legal norms. This study examines the issue using a normative legal research method (doctrinal approach), by analyzing relevant legal norms both written in legislation, legal doctrines, court decisions, and fundamental legal principles. The findings indicate that systematic bullying violates core ethical principles, such as the principle of non-maleficence (do no harm), justice, and respect for individual dignity. Furthermore, these practices contradict the constitutional rights of learners as guaranteed under Indonesia’s legal system. The absence of specific regulations protecting residents further exacerbates the power imbalance within medical education. Therefore, this study advocates for comprehensive reform, including the establishment of a safe and reliable reporting system, stronger legal protections for residents, and the integration of ethical values education into the medical curriculum.